2011
DOI: 10.1111/j.1365-2621.2011.02880.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of made‐in‐transit set culture yoghurt: effect of increasing the concentration of reconstituted skim milk as the milk base

Abstract: The fermentation time, yoghurt acidity expressed as lactic acid, starter culture growth, viscosity and firmness of made-in-transit (MIT) set culture yoghurt produced using different concentrations of reconstituted skim milk powder (SMP) from 12% to 20% (w ⁄ v) as the milk base were investigated. All milk base formulations were ultra-high temperature sterilised at 138°C for 6 s. The results revealed that increasing the SMP concentration increased the viscosity and firmness of MIT set culture yoghurt. At 20% SMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Sodini et al (2002) observed that a mixed culture of STLA produced a fermentation time of approximately 4 to 8 h compared with LA by itself which had a fermentation time of 8 to 13 h. In another study, Damin, Minowa, Alcantara, and Oliveira (2008) found the shortest fermentation time to reach pH 4.5 was obtained with milk fermented by S. thermophiles with L. bulgaricus (5.4 h), and that the fermentation time was longer time when S. thermophiles was co-cultured with Bifidobacterium lactis (8.3 h) and L. acidophilus (9.3 h); the differences between them were significant (p < 0.05). The combination of STLA was found to extend the yoghurt fermentation to 168 h when incubated at 25 o C compared to STLB (Nor-Khaizura et al, 2012). Probiotics tend to grow slowly in yoghurt milk base, do not compete well with many starter strains and the probiotics show poor stability during storage.…”
Section: Denaturation Of Whey Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodini et al (2002) observed that a mixed culture of STLA produced a fermentation time of approximately 4 to 8 h compared with LA by itself which had a fermentation time of 8 to 13 h. In another study, Damin, Minowa, Alcantara, and Oliveira (2008) found the shortest fermentation time to reach pH 4.5 was obtained with milk fermented by S. thermophiles with L. bulgaricus (5.4 h), and that the fermentation time was longer time when S. thermophiles was co-cultured with Bifidobacterium lactis (8.3 h) and L. acidophilus (9.3 h); the differences between them were significant (p < 0.05). The combination of STLA was found to extend the yoghurt fermentation to 168 h when incubated at 25 o C compared to STLB (Nor-Khaizura et al, 2012). Probiotics tend to grow slowly in yoghurt milk base, do not compete well with many starter strains and the probiotics show poor stability during storage.…”
Section: Denaturation Of Whey Proteinmentioning
confidence: 99%
“…Caseins are insolubilized protein and begin to precipitate when the pH of milk is reduced to pH 4.6. The soluble portion at pH 4.6 is known as whey proteins consisting of albumins and globulins (Chandan & O'Rell, 2006).The total solids content of the milk base influences the yoghurt firmness (Penna, Converti, & De Oliveira, 2006;Tamime & Deeth, 1980;Nor-Khaizura et al, 2012). The milk base protein content (Tamime, Kalab, & Davies, 1984;Trachoo & Mistry, 1998) and protein type (Cho, Lucey, & Singh, 1999;Penna et al, 2006;Sodini, Remeuf, Haddad, & Georges, 2004;Tamime et al, 1984) are important factors in determining yoghurt texture.…”
Section: Milk Standardizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Soukoulis et al (2007) found yoghurt fortified with MPC produced a product with a better texture than that produced through the addition of whey protein. Isleten and Karagul-Yuceer (2006) and Nor-Khaizura et al (2012) reported that yogurts fortified with NaCN exhibited better physical and sensory properties than control yoghurts. Yoghurts made with other casein-based ingredients were found firmer, with less syneresis, than yoghurts that were fortified at the same protein level with whey protein-based ingredients (Modler et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Fortification of the skim milk base with milk protein concentrate (MPC) or sodium caseinate (NaCN) improves the firmness of yoghurt, and syneresis decreases as the protein content increases (Nor-Khaizura et al, 2012, Schkoda, Hechler, & Hinrichs, 2001. Soukoulis et al (2007) found yoghurt fortified with MPC produced a product with a better texture than that produced through the addition of whey protein.…”
Section: Introductionmentioning
confidence: 99%